ENHANCING EMPLOYEE ORAL COMMUNICATION COMPETENCE THROUGH HOSPITALITY ENGLISH TRAINING AT MEXOLIE HOTEL, KEBUMEN: Education - firharmawan, hastri; Andika, Alek; Garwan, Hellaisna Nuraini; Mitsalina, Endah; Asroriyah, Atik Muhimatun; Heriyanto, Dwi (Politeknik Negeri Lampung, 2022)
Improving service quality is one of the supporting factors to winning the increasingly competitive globalcompetition in the hospitality world. Communication skills, especially speaking, are demanded for ahotel to have a good image in front of consumers. However, not all hotels have human resources with good communication skills. This community service aims to improve communication skills in English,especially speaking skills for employees at the Mexolie hotel, Kebumen. The method of training wasconducted by lecturing, demonstrating, and role playing. Theme covers hotel services and handlingcomplaints. The training participants consisted of 10 employees from the front office andhousekeeping departments. The results of the training show that there is an increase in the ability ofemployees to speak English fluently. This is known from the results of the average pretest score of58.8 while the posttest average value is 75.6. The training has been effective because it can improvethe communication competence of the employees of the Mexolie Hotel, Kebumen so that it supportsthe increase in professionalism in carrying out daily tasks in the workplace. As a follow-up, it issuggested that the hotel hold an English zone to familiarize employees with applying their knowledgein using English in the work environment.